Non-Refoulement, Environmental Displacement, and the Limits of State Sovereignty: Legal Obligations Beyond the Refugee Convention Framework - Taty Sugiarti; Ihsanul Maarif (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The principle of non-refoulement is traditionally associated with Article 33 of the 1951 Refugee Convention, yet contemporary displacement increasingly occurs outside the classical refugee framework. In addition to persecution and armed conflict, people may be forced to move because of environmental degradation, climate-related disasters, ecological vulnerability, loss of livelihood, and conditions that threaten human dignity and survival. This article examines how non-refoulement develops beyond the Refugee Convention, particularly in relation to environmental displacement and the limits of State sovereignty. It addresses three research questions: how non-refoulement operates under customary international law and international human rights law; to what extent its core content may be linked to jus cogens; and how it limits State discretion in migration control, environmental governance, and protection of displaced persons. This study uses normative legal research with statutory, conceptual, and case-law approaches. It examines international treaties, human rights instruments, environmental law principles, peremptory norms, judicial decisions, and recent scholarship on externalized migration control and climate-induced displacement. The findings show that non-refoulement functions as a multi-source obligation through three layers: the customary baseline binding all States, the human rights non-derogability layer protecting all persons from irreparable harm, and the jus cogens core prohibiting removal to peremptory violations such as torture, genocide, slavery, and crimes against humanity. The article contributes by formulating a three-layer normative convergence test and by linking non-refoulement to environmental displacement, sustainable development, and the legal limits of sovereignty.